Development of a Real-Time PCR based protocol for quantifying Radopholus similis in field samples - S J Eapen, P B Krishna, (Journal of Spices and Aromatic Crops, 2019)
The burrowing nematode, Radopholus similis, is an obligate migratory endoparasite. Currently detection of this nematode is carried out mostly by physically extracting them from soil and then observing under a light microscope. To identify this nematode, a thorough knowledge about their morphological features is quite indispensable. Developing a DNA based detection technique makes it more convenient and accurate in detection. Though PCR based methods have been reported by earlier workers, developing a Real-Time PCR based method will enable estimating their population in field samples. In this study, Real-Time PCR primers were designed using the DNA sequences from the ITS region of R. similis. It can detect R. similis up to the limit of 100 fg μL-1 DNA. The real time PCR based detection serves as an efficient tool for the detection and estimation of this nematode from soil samples.